Translating Culture. Oscar Wilde’s Decadent Expression into Latvian - Ilze Kačāne (Lea)
The paper is a comparative study of translating decadence-related cultural concepts encountered in The Picture of Dorian Gray into Latvian and compares the first translation of the novel by Jānis Ezeriņš (1920) with that produced thirteen years later by Roberts Kroders (1933). As a result of a mutual “competition” between the two Latvian versions, the translation by Ezeriņš, known as the “Latvian Wilde”, has become not only a springboard for the Latvian writers searching for a modern style of expression but also a significant contribution to the reception of Aestheticism and wider recognition of decadent style.